Generation and consistency checking of design and program structures - Lichtman, Z. L. (IEEE transactions on software engineering, 1986)
The author describes a mini methodology for generation and representation of design and program structures and for structural consistency checking between two successive designs or between a design and a program. This methodology comprises a tool (Program Design Language), a representation, and consistency criteria. The Program Design Language (PDL) extracts structure information, in a controlled way, from the top level program design, through layers of detailed designs, down to the source code itself. It generates an actual, complete, concise, and easily comparable structure representation. Structural consistency between levels can be checked, both at the development phase and at the operation and maintenance phase, ensuring continued structural consistency between the design(s) and the program.